2019
DOI: 10.1111/desc.12892
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in neonatal “imitation” fail to predict early social cognitive behaviour

Abstract: The influential hypothesis that humans imitate from birth – and that this capacity is foundational to social cognition – is currently being challenged from several angles. Most prominently, the largest and most comprehensive longitudinal study of neonatal imitation to date failed to find evidence that neonates copied any of nine actions at any of four time points (Oostenbroek et al., [2016] Current Biology, 26, 1334–1338). The authors of an alternative and statistically liberal post‐hoc analysis of these same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 83 publications
(226 reference statements)
0
3
0
Order By: Relevance
“…Our behavioral evaluations of infant imitation also evidenced no group differences, perhaps because we found no evidence that any of the infants imitated. Although other groups do find evidence of imitation in neonates using this task (34,98), when data are re-analyzed in ways that ensure that infants are making meaningful responses that differ from chance (called cross-target analyses), these claims do not hold (81,99). As a result, it is unclear whether rhesus neonates actually imitate in general and whether performance on this task is meaningful.…”
Section: Discussionmentioning
confidence: 97%
“…Our behavioral evaluations of infant imitation also evidenced no group differences, perhaps because we found no evidence that any of the infants imitated. Although other groups do find evidence of imitation in neonates using this task (34,98), when data are re-analyzed in ways that ensure that infants are making meaningful responses that differ from chance (called cross-target analyses), these claims do not hold (81,99). As a result, it is unclear whether rhesus neonates actually imitate in general and whether performance on this task is meaningful.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, others report infants’ gaze following skills are somewhat developmentally stable at early ages, but this stability appears to be relatively small (e.g., r = .20 from 6 to 10 months; Astor et al., 2020; ρ = .37 from 8 to 12 months; Schietecatte et al., 2012). Interestingly, another study failed to detect stable individual differences in a variety of social cognitive skills in the first year (Redshaw et al., 2020). Together, these findings indicate rapid changes to social cognitive skills in early infancy may make it difficult to consistently detect stable individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, authors of the largest ever longitudinal study of human neonatal imitation (Oostenbroek et al, 2016) reported that 106 neonates failed to imitate any of nine gestures at any of four time points between 1 and 9 weeks of age. Although this study was originally aimed at uncovering whether neonatal imitation predicted later social cognitive capacities (see Redshaw et al, 2020; Suddendorf, Oostenbroek, Nielsen, & Slaughter, 2013), the results have been interpreted as a compelling and perhaps fatal challenge to the existence of the phenomenon itself (Heyes, 2016b). In response, a group of 13 prominent neonatal-imitation researchers published a detailed critique, arguing that the unsuccessful replication attempts could be explained by specific methodological choices (Meltzoff et al, 2018; see Table 1).…”
Section: Neonatal Imitation: History and Controversymentioning
confidence: 99%